Unknown Work of Chronicler Ahmed Lutfî Efendi: Sûrnâme - Sercan Kadaş (Türkiyat Mecmuası)
Lutfî EFfendi, one of the last palace historians of the Ottoman Empire, served as a chronicler for the longest time, and he continued his duty as a chronicler until his death in 1907, when he was appointed in 1866. Ahmed Lutfî EFfendi became, who became famous with the Târih-i Lutfî he presented to II. Abdülhamid is, also known for his works in literature, language, and education. It has been determined that his work, Sûrnâme, about which there is no information in any source, was preserved in a separate manuscript together with the author's calligraphy. Sûrnâme, which he wrote in 1300-1301/1882-1883, is about the circumcision weddings of II. Abdülhamid’s princes Mehmed Seyfeddîn, Mehmed Selîm, Abdülmecîd and Mehmed Şevket. Ahmed Lutfî EFfendi expressed his observations about the sûr, which is also available in archive documents; He enriched it with couplets, stanzas, and historical poems. He evaluated the historical, cultural, and economic situation of the period and the old sûr ceremonies. Sûrnâme reflects the change in the genre of sûr-i hümâyûn, which was the indicator of the magnificence of the empire for many years, and sûrnâme, which is the historical and literary record of these ceremonies. This work, which can be considered among the last examples of authored sûrnâmes, which are important sources of our cultural history, will be introduced for the first time; Form, content, and stylistic features will be examined and presented with a translation.